Influence of InP coupling cavity on Fano resonance of sub wavelength MIM waveguide - Shihao Ban (Nature Portfolio, 2021)
Abstract In this paper, influence of InP coupling cavity on Fano resonance of sub wavelength MIM waveguide was studied by FDTD. It was observed that the resonant wavelengths of mode mj (j = 1, 2, 3) were closely related with the height H 2 of InP coupling cavity. In addition, before and after the addition of air cavity, the relative farfield intensities I was a function of height H 2. Therefore, InP as discrete state could be used as the filling dielectrics of Fano resonance in the MIM waveguide.